2022
DOI: 10.3389/fnut.2022.913883
|View full text |Cite
|
Sign up to set email alerts
|

The Structure Basis of Phytochemicals as Metabolic Signals for Combating Obesity

Abstract: The consumption of phytochemicals, bioactive compounds in fruits and vegetables, has been demonstrated to ameliorate obesity and related metabolic symptoms by regulating specific metabolic pathways. This review summarizes the progress made in our understanding of the potential of phytochemicals as metabolic signals: we discuss herein selected molecular mechanisms which are involved in the occurrence of obesity that may be regulated by phytochemicals. The focus of our review highlights the regulation of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 184 publications
1
7
0
Order By: Relevance
“…There are various hypotheses about how a plant-based diet may help maintain a healthy body weight. First, a plant-based diet has a lower energy density, resulting in greater satiety and lower energy consumption [ 22 , 36 ]. Furthermore, plant-based diets contain lower fat and higher fiber, which may impact the microbiome, which is known to have substantive impacts on energy utilization in humans [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various hypotheses about how a plant-based diet may help maintain a healthy body weight. First, a plant-based diet has a lower energy density, resulting in greater satiety and lower energy consumption [ 22 , 36 ]. Furthermore, plant-based diets contain lower fat and higher fiber, which may impact the microbiome, which is known to have substantive impacts on energy utilization in humans [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Models 1 and 2 indicated the results with different covariates. Ten-fold cross-validation was also checked for cross-validation consistency (CVC) because the sample size was larger than 1000 [ 22 ]. In total, 10 out of 10 in the CVC met the perfect cross-validation criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics of the continuous variables were analyzed as the adjusted means with standard deviations after adjusting for the covariates. The statistical differences among the gender and insulin resistance groups were compared using a two-way analysis of covariance (ANCOVA) [19]. Multiple comparisons of the groups were performed using a Tukey's test.…”
Section: Discussionmentioning
confidence: 99%
“…However, the microbiome research has not progressed to the point that changes in the gut microbiome can be considered a cause or cure for excess body weight. There is also evidence that various phytochemicals from plant-based foods and dietary supplements may have antiobesity effects by various mechanisms [19]. It has been shown that the anti-in ammatory properties of plant-based diets can prevent obesity and even result in a healthier obese phenotype in people who become obese [36].…”
Section: Discussionmentioning
confidence: 99%
“…Biologically active phytochemicals are compounds with diverse chemical structures found in plants that exert many health beneficial biological effects and possess diverse molecular mechanisms including epigenetics ( Table 1 ) ( Fang et al, 2003 ; Chen et al, 2004 ; Fang et al, 2005 ; Druesne-Pecollo et al, 2007 ; Choi et al, 2009 ; Ho et al, 2009 ; Balasubramanian et al, 2010 ; Wu et al, 2011 ; Gong et al, 2012 ; An et al, 2013 ; Kang et al, 2013 ; Wang et al, 2014 ; Guo et al, 2015 ; Jiang et al, 2016 ; Kala and Tollefsbol, 2016 ; Li et al, 2017b ; Gao and Tollefsbol, 2018 ; Cremonini et al, 2019 ; Kuo et al, 2019 ; Yang et al, 2019 ; Wu et al, 2020 ). For a long time, they have been used for the protection and treatment of various diseases, such as diabetic nephropathy ( Hudlikar et al, 2021 ), obesity ( Martin et al, 2013 ; Dincer and Yuksel, 2021 ; Li et al, 2022c ), and cancer ( Lee et al, 2011 ; Kotecha et al, 2016 ). In general, mounting evidence shows that dietary phytochemicals are potent chemopreventive/cancer interceptive agents due to their antioxidant, metabolic modulation, and epigenetic regulation properties ( Gerhauser, 2013 ; Thakur et al, 2014 ; Russo et al, 2017 ; Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%